NOMINAL OPERATING TEMPERATURE OF PHOTOVOLTAIC CELLS IN SOLAR ENERGY – NOCT STANDARD: LIC, HTC, LTC CONDITIONS (KIUT Publication, 2025)
This article discusses important standards for evaluating the efficiency of solar panels under real operating conditions – NOCT, LIC, HTC, and LTC. The authors analyze the essence of the NOCT (Nominal Operating Cell Temperature) standard, its differences from other standards such as STC and PTC, and aspects related to module design and temperature stability. The article provides guidance for making informed decisions when selecting solar panels based on performance under high and low temperatures as well as low irradiance conditions. It also emphasizes the importance of considering temperature-dependent energy losses and the real efficiency of the modules.